Valid across-group comparisons with labeled scales: the gLMS versus magnitude matching - Bartoshuk, L.M; Duffy, V.B; Green, B.G; Hoffman, H.J; Ko, C.-W; Lucchina, L.A; Marks, L.E; Snyder, D.J; Weiffenbach, J.M (Physiology & behavior, 2004)
Labeled scales are commonly used for across-group comparisons. The labels consist of adjective/adverb intensity descriptors (e.g., “very strong”). The relative distances among descriptors are essentially constant but the absolute perceived intensities they denote vary with the domain to which they are applied (e.g., a “very strong” rose odor is weaker than a “very strong” headache), as if descriptors were printed on an elastic ruler that compresses or expands to fit the domain of interest. Variation in individual experience also causes the elastic ruler to compress or expand. Taste varies genetically: supertasters perceive the most intense tastes; nontasters, the weakest; and medium tasters, intermediate tastes. Taste intensity descriptors on conventional-labeled scales denote different absolute perceived intensities to the three groups making comparisons across the groups invalid. Magnitude matching provides valid comparisons by asking subjects to express tastes relative to a standard not related to taste (e.g., supertasters match tastes to louder sounds than do nontasters). Borrowing the logic of magnitude matching, we constructed a labeled scale using descriptors unrelated to taste. We reasoned that expressing tastes on a scale labeled in terms of all sensory experience might work. We generalized an existing scale, the Labeled Magnitude Scale (LMS), by placing the label “strongest imaginable sensation of any kind” at the top. One hundred subjects rated tastes and tones using the generalized LMS (gLMS) and magnitude matching. The two methods produced similar results suggesting that the gLMS is valid for taste comparisons across nontasters, medium tasters, and supertasters.